(untitled) (Revista UTCiencia: i-ISSN: 1390-6909. e-ISSN: 2602-8263, 2026)
This research aims to analyze the impact of school–family co-responsibility on the educational process of students with hearing disabilities at the Unidad Educativa Especializada Cotopaxi during the 2025–2026 academic year, from the perspective of the National Bilingual Bicultural Educational Model. The study adopts a qualitative approach framed within the interpretative paradigm. Data collection was conducted through structured interviews and focus groups involving school authorities, teachers, students, and representatives of the Unidad Educativa Especializada Cotopaxi (UEEC), Hearing Disability Area, in order to understand the dynamics of the relationships established among these actors. Their perspectives were triangulated in light of dimensions and categories derived from the National Bilingual Bicultural Educational Model (MENBB). In the case of participants with hearing disabilities, data were collected using Ecuadorian Sign Language (LSEC) with the support of an interpreter. The collected data were systematized in content matrices, which allowed for the orderly extraction of results. Among the main findings, it is evident that the UEEC efficiently manages the education of students with hearing disabilities using the available public resources; however, these resources are insufficient to meet all the technical requirements established by the MENBB. Additional classrooms, teachers per grade level, and laboratories are needed. At the curricular level, guidelines related to planning, Ecuadorian Sign Language (LSEC), and written Spanish are appropriately implemented. Parents and students positively value the institutional work. Nevertheless, teachers consider greater family support necessary, particularly in the acquisition of Ecuadorian Sign Language, to ensure the learning outcomes established in the curriculum.